Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/molecules24224180
|View full text |Cite
|
Sign up to set email alerts
|

Key-Marker Volatile Compounds in Aromatic Rice (Oryza sativa) Grains: An HS-SPME Extraction Method Combined with GC×GC-TOFMS

Abstract: The aroma of rice essentially contributes to the quality of rice grains. For some varieties, their aroma properties really drive consumer preferences. In this paper, using a dynamic headspace solid-phase microextraction (HS-SPME) system coupled to a two-dimensional gas chromatography (GC×GC) using a time-of-flight mass spectrometric detector (TOFMS) and multivariate analysis, the volatile compounds of aromatic and non-aromatic rice grains were contrasted to define some chemical markers. Fifty-one volatile comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 42 publications
0
18
1
2
Order By: Relevance
“…This could possibly be construed to imply that not all volatile biochemical markers are aroma active compounds. This would be in contrast to the study by Setyaningsih et al (2019) in which all the seven volatile biochemical markers were aroma active compounds. Hence, the present study deemed it necessary to further refine the list of possible volatile biochemical markers by subjecting the VOCs to correlation and regression analyses.…”
Section: Volatile Organic Compounds Able To Differentiate Non-aromaticontrasting
confidence: 63%
See 2 more Smart Citations
“…This could possibly be construed to imply that not all volatile biochemical markers are aroma active compounds. This would be in contrast to the study by Setyaningsih et al (2019) in which all the seven volatile biochemical markers were aroma active compounds. Hence, the present study deemed it necessary to further refine the list of possible volatile biochemical markers by subjecting the VOCs to correlation and regression analyses.…”
Section: Volatile Organic Compounds Able To Differentiate Non-aromaticontrasting
confidence: 63%
“…Further multivariate analyses revealed; toluene; 2,3-dioxabicyclo[2.2.1]heptane, 1-methyl-; hydroxylamine, O-decyl-; ethanol, 2-butoxy; undecane, 2,6-dimethyl; methyl acetoacetate; 1-hexanol, 2-ethyl; benzene, 1,2,3-trimethyl-; heptane, 2,2,4,6,6-pentamethyl-and benzene, 1,2,4,5-tetramethyl-as candidates for volatile biochemical markers of the rice aroma trait. With the exception of 2-ethyl hexanol, all identified volatile markers in the three studies were not similar (Griglione et al, 2015;Setyaningsih et al, 2019). Importantly, careful examination of all earlier reported volatile markers indicated that the compounds were aroma active.…”
Section: Possible Volatile Biochemical Markers For the Rice Aroma Traitmentioning
confidence: 80%
See 1 more Smart Citation
“…Maka dari itu, penelitian ini bertujuan mencari senyawa marker (penanda) dari kulit ari biji kopi robusta (C. robusta) yang mampu menjadi standar kualitas senyawa yang dicari untuk bahan baku produk absorbent dengan metode GC-MS. Kedepannya, senyawa marker (penanda) akan mampu digunakan oleh berbagai produsen yang menggunakan kulit ari biji kopi robusta sebagai bahan baku produk absorbent sekaligus pengharum natural sebagai bentuk quality control produk yang dihasilkan [6]. Komponen volatile yang ditemukan melalui GC-MS tergolong sebagai prediksi komponen dan ke depannya akan dipelajari lebih lanjut.…”
Section: Pendahuluanunclassified
“…Furthermore, hexanal, octanal, nonanal, ( E )-2-octenal, decanal, 1-heptanol, and 1-octanol were identified as major aroma-active compounds in Jasmine rice [ 11 ]. Widiastuti et al [ 12 ] using a dynamic headspace solid-phase extraction system coupled to a two-dimensional gas chromatography (GC × GC) coupled with a time-of-flight mass spectrometric detector (TOFMS) to distinguish the aromatic from non-aromatic rice grains. Fifty one kinds of volatile compounds were detected by this methods, and eight key-marker volatile compounds (i.e., pentanal, hexanal, 2-pentylfuran, 2,4-nonadienal, pyridine, 1-octen-3-ol and ( E )-2-octenal) were selected for identifying the aromatic rice of Indonesia.…”
Section: Introductionmentioning
confidence: 99%